Cause-specific mortality in osteoarthritis of peripheral joints. Issue 6 (June 2019) - Turkiewicz, A.; Kiadaliri, A.A.; Englund, M.
Summary: Purpose: To estimate cause-specific mortality in osteoarthritis patients compared to the general population. Methods: We identified all residents in southern Sweden aged 45–84 years in 2003. Through the Skåne Healthcare Register (SHR) we identified those diagnosed with osteoarthritis in peripheral joints between 1998 and 2003. We followed all residents from 2004 until relocation outside of the region, death, or end of 2014. We classified the underlying cause of death from death certificates into: cardiovascular and neoplasms, diabetes, infections, dementia, diseases of digestive system, or other causes. For estimation, we used multi-state adjusted Cox proportional hazards models. Results: We identified 15, 901 patients (mean age [SD] 67 years [10], 41% men) with prevalent doctor-diagnosed osteoarthritis in knee, 9347 in hip, 4004 in hand and 5447 in other peripheral joints among 469, 177 residents. For most causes of death in osteoarthritis patients, we found no increased mortality, with hazard ratios (HRs) close to 1, similar for men and women. However, for knee and hip osteoarthritis and cardiovascular death, HRs were non proportional and increased to 1.19 (95%CI 1.10, 1.28) and 1.13 (1.03, 1.24) during 9–11 years of follow-up, mostly due to excess mortality from chronic ischemic heart diseases and heart failure. Conclusions: The risk of cardiovascular excess deaths increases with duration of knee and hip osteoarthritis. The major contributors are chronic ischemic heart diseases and heart failure. Our results call for improved implementation of osteoarthritis treatment guidelines, with major focus on interventions to address mobility limitations and maintaining or increase physical activity level.